AN INTERDISCIPLINARY APPROACH METHODOLOGY FOR THE STUDY OF BILINGUISM (Scientific journal of the Fergana State University, 2025)
This article analyzes the interdisciplinary approach to studying bilingualism. It emphasizes the growing importance of linguistic communication in Uzbekistan, driven by the rapid development of science and technology, the integration of the internet into daily life, and the country's increasing political and cultural ties with other nations. The article traces the historical development of bilingualism, exploring its emergence in ancient migrations, trade, and invasions, and the subsequent academic attention it received starting in the 19th century. The paper examines the methodological foundations laid in the study of bilingualism, particularly in relation to psycholinguistics, historical linguistics, and didactics. The research highlights how bilingualism has evolved into a significant field within linguistics and education.